Elevated temperature and toxic Microcystis reduce Daphnia fitness and modulate gut microbiota. (15th February 2021) - Akbar, Siddiq; Huang, Jing; Zhou, Qiming; Gu, Lei; Sun, Yunfei; Zhang, Lu; Lyu, Kai; Yang, Zhou
Abstract: The gut microbiota has been increasingly recognized to regulate host fitness, which in turn is dependent on stability of community structure and composition. Many biotic and abiotic factors have been demonstrated to shape gut microbiota of cladocerans. However, the interactive effects of these variables on cladocerans fitness due to alteration of gut microbiota and their linkage with life history parameters are poorly understood. Here, we investigated the responses of Daphnia magna gut microbiota to the combined effects of toxic Microcystis aeruginos a and high temperature and its associations with fitness. We found that under good food regime, the temperature has no effect on the composition of the gut microbiota, whereas under high proportion of toxic M. aeruginosa and high temperature conditions, D. magna lost their symbionts. High proportion of toxic M. aeruginosa and high temperature had synergistically negative effects on D. magna performance due to altered gut microbiota. The high abundance of symbiotic Comamonadaceae and good food increased D. magna fitness. The present study illustrates that understanding life history strategies in response to multiple stressors related to changes in the gut microbiota diversity and composition requires integrated approaches that incorporate multiple linked traits and tether them to one another. Graphical abstract: Image 1 Highlights: Elevated temperature and toxic Microcystis reduce Daphnia growth and survival. High temperature and Microcystis reduce Daphnia fitness by altering gut microbiota. Daphnia fitness was correlated with the abundance of Comamonadaceae and good food. Life history parameters were linked with the changes in the Daphnia gut microbiota. Abstract : High temperature and toxic Microcystis aeruginosa reduce Daphnia magna fitness by altering the composition and abundance of its gut microbiota.